Evaluation of the nutritional status of older hospitalised geriatric patients: a comparative analysis of a Mini Nutritional Assessment (MNA) version and the Nutritional Risk Screening (NRS 2002) - Christner, S.; Ritt, M.; Volkert, Dorothee; Wirth, Rainer; Sieber, Cornel; Gaßmann, Karl-Günter (Journal of Human Nutrition and Dietetics, 2016)
BackgroundThe present study aimed to evaluate a short-form (MNA-SF) version of the Mini Nutritional Assessment (MNA), in which some of the items were operationalised, based on scores from tools used for a comprehensive geriatric assessment, as a method for analysing the nutritional status of hospitalised geriatric patients. We compared this MNA-SF version with the corresponding MNA long-form (MNA-LF) and Nutritional Risk Screening 2002 (NRS 2002) in terms of completion rate, prevalence and agreement regarding malnutrition and/or the risk of this.MethodsIn total, 201 patients aged 65years who were hospitalised in geriatric wards were included in this analysis.ResultsThe MNA-SF, MNA-LF and NRS 2002 were completed in 98.0%, 95.5% and 99.5% of patients (P=0.06), respectively. The MNA-SF, MNA-LF and NRS 2002 categorised 93.4%, 91.1% and 66.0% of patients as being malnourished or at risk of being malnourished (P<0.001). Agreement between the MNA-SF and MNA-LF was substantial (=0.70, P<0.001). No agreement between the MNA-SF and NRS 2002 was found (=-0.12, P<0.001). Interestingly, NRS 2002 part 1 (prescreening) revealed a false negative rate of 21.0% (only in patients aged 70years who showed moderate disease severity) in relation to the NRS 2002 part 2.ConclusionsThe MNA-SF version emerged as a useful tool for evaluating the nutritional status of hospitalised geriatric patients. The NRS 2002 part 1 showed limited value as a prescreening aid in relation to the NRS 2002 part 2 in the same group of patients.
Keywords: clinical nutrition; malnutrition; nutrition screening; nutritional assessment